The Relationship between English Teacher’s Praise and English Learning Achievement of The Tenth Grade of SMK Negeri 9 Samarinda - Rachman, Dzul; Nur, Dedi Rahman (LPPM Universitas Mercu Buana Yogyakarta, 2017)
Reinforcement is one of the strategies in classroom management, which is familiar among teachers. One of the types of reinforcement in social reinforcement is praise. Praise can function as a tool for instruction and for increasing social and academic behaviors. To be effective, the student must view the attention provided through praise as pleasurable or motivational. The design of this study was correlation design. The research participant was the tenth grade students of SMK Negeri 9 Samarinda. The purposes of this study are to find out how is relationship between the teacher’s praise and the English learning achievement tenth grade of SMK Negeri 9 Samarinda and is there any significant relationship between English teacher’s praise and English learning achievement. The researcher conducted observation for a month, distributed questionnaires and collected the result of achievement test from the teacher, as the instruments of this study. Then the collected data were analyzed in order to find out the manifestation of reinforcement applied by the teacher. After analyzing the data gained through the observation, the researcher found out that English teacher praise significantly correlate with the English learning achievement of tenth grade SMK Negeri 9 Samarinda (r-value: 0,442 > r-table: 0,334). From the questionnaire, it was found that the students showed positive response or opinion toward the implementation of reinforcement in their class for example teacher praises immediately, frequently, enthusiastically, by using eye contact, uses many kinds of word praise and explains the reason why he praises students.